2020
DOI: 10.5797/jnet.cr.2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Carotid Artery Stenting after Aspiration of Thrombus and Unstable Plaque

Abstract: There is no established method for carotid artery stenting (CAS) for internal carotid artery stenosis with vulnerable plaque and thrombosis. We report a case in which CAS was performed by aspiration using the Penumbra system for thrombosis that increased in the subacute phase in symptomatic cervical internal carotid artery stenosis. Case Presentations: A 59-year-old man with a history of lacunar infarction visited the emergency department with weakness in the right upper limb. He was admitted for cerebral infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recently, in addition to conventional treatments, endovascular thrombectomy for carotid FFT has been reported [2,4,5,[7][8][9][10][11][12][13][14]. However, when balloon protection is used for distal protection, complete interruption of the ICA flow is undesirable in patients without hemodynamic intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in addition to conventional treatments, endovascular thrombectomy for carotid FFT has been reported [2,4,5,[7][8][9][10][11][12][13][14]. However, when balloon protection is used for distal protection, complete interruption of the ICA flow is undesirable in patients without hemodynamic intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Fitzpatrick et al 6) and Giragani et al 8) performed treatment using a stent retriever by combining proximal balloon protection or distal filter protection, and they were able to remove the FFT without complications. Otawa et al 9) and Kubo et al 10) reported cases in which the FFT was removed by aspiration using an aspiration catheter followed by CAS applied to the residual lesion. Carr et al reported a case in which ADAPT was performed for the first pass, but it was only partially removed; therefore, they used the technique combining a stent retriever and an aspiration catheter for the second pass, and the FFT was able to be completely removed without complications.…”
Section: Discussionmentioning
confidence: 99%